Development of the statistical approach to the calculation of building structures - Pichugin, Sergii (Academic journal Industrial Machine Building Civil Engineering, 2025)
The current method of calculating building structures by limit states (previously by allowable stresses) is essentially semi-probabilistic.  Meanwhile, in parallel with this dual method, for many years, fully probabilistic (statistical) approaches to the calculations have been developed. The aim of the article is to consistently review the approaches developed over the course of ninety years to the implementation of general probabilistic methods for calculating building structures, starting from the 1930s to the present. It is emphasized that domestic specialists are actively developing probabilistic methods, the results of which are implemented in regulatory documents. The prospects of the results of this scientific direction in creating a new generation of building design standards are noted.
Keywords: probabilistic methods; design codes; statistical methods; safety factor; limit states